BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2002)
Guava Diseases .(An annotated bibliography 1907-1990). By A.K. Misra and am Prakash. Publishers : Bishen Singh and Mahendra Pal Singh, Dehradun. 1994. pp. 132. 'Detection of Plant Pathogens and their Management' Edited by J.P. Verma, Anupam Varma and Dinesh Kumar, Angkor Publishers(P) Ltd., New Delhi, 1-475 pp. Prices Rs. 475.